Given :
![x^2\text{ - 4x + 9 = 0}](https://img.qammunity.org/2023/formulas/mathematics/college/masl4m7h2i1enlq4yttto89c0be7urgrlh.png)
Solution
To find the roots of the equation, we can try factorizing the expression by the left.
The factors of 9 are 3,3 or 1, 9. Each of these cannot work.
So, we use the quadratic formula instead.
Given the general form of a quadratic equation:
![ax^2\text{ + bx + c = 0}](https://img.qammunity.org/2023/formulas/mathematics/college/5g12tkramqxsv41d83rhxbcqeorituzjv5.png)
The quadratic formula to find the roots of the equation is given as:
![\text{x = }\frac{-b\text{ }\pm\sqrt[]{b^2-4ac}}{2a}](https://img.qammunity.org/2023/formulas/mathematics/college/drkh334eunntl2hq47yrsf1mly00hzex3d.png)
Comparing the standard form with the given equation, we have:
a = 1 , b = -4, c =9
Substituting this into the quadratic formula:
![\begin{gathered} x\text{ = }\frac{-(-4)\text{ }\pm\sqrt[]{(-4)^2-\text{ 4}*1*9}}{2\text{ }*\text{ 1}} \\ =\text{ }\frac{4\text{ }\pm\text{ }\sqrt[]{-20}}{2} \\ =\text{ }\frac{4\text{ }\pm\text{ }\sqrt[]{4\text{ }*\text{ -5}}}{2} \\ =\text{ }\frac{4\text{ }\pm\text{ 2}\sqrt[]{-5}}{2} \\ =\text{ }\frac{4\text{ }\pm\text{ 2}\sqrt[]{5}i}{2} \\ \text{recall that i = }\sqrt[]{-1} \\ x\text{ = 2 }\pm\text{ i}\sqrt[]{5} \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/ii661v5fkqwxnr70ldte9xj975lv2l3gi9.png)
Answer: Option B